Pengembangan model manajemen Ma’had Al-Jami’ah IAIN Surakarta - Hafidah, Hafidah; Makruf, Imam (Ta’dibuna: Jurnal Pendidikan Islam, 2020)
This study aims to produce a guide to the management model of Ma’had al Jami’ah that is appropriate in IAIN Surakarta. This research uses a mixed-method approach that combines quantitative and qualitative approaches. Data collected through questionnaires, interviews, observations, and documentation. Then the data is elaborated and validated through FGD and triangulation. The data analysis is carried out with an interactive model. The results of this study indicate that 1) all stakeholders consider the Surakarta IAIN to have the Ma’had Al-Jami’ah program because of the strategic position of the Surakarta IAIN,; 2) Relevant programs are developed under the vision and mission of the institute, as well as the objectives of conducting education and the established competency standards of graduates; 3) The Ma’had Al-Jami’ah program is managed by a technical implementation unit under the coordination of the Vice Chancellor for Student Affairs; 4) strategies that can be taken to realize the Ma’had Al-Jami’ah management model that is relevant to IAIN Surakarta are involving the elements of higher education and Quality Assurance Institutions supported by the existence of an MOU or cooperating with nearby pesantren. Abstrak Penelitian ini bertujuan untuk menghasilkan panduan model manajemen Ma’had al Jami’ah yang tepat diterapkan di IAIN Surakarta. Penelitian ini menggunakan pendekatan mixed methode yang menggabungkan antara pendekatan kuantitatif dan kualitatif. Data dikumpulkan melalui angket, wawancara, observasi, dan dokumentasi. Data dielaborasi dan divalidasi melalui FGD dan triangulasi. Analisis data dilakukan dengan model interaktif. Hasil penelitian ini menunjukkan bahwa 1) semua stakeholder menganggap IAIN Surakarta perlu memiliki program Ma’had Al-Jami’ah karena posisi strategis IAIN Surakarta; 2) Program yang relevan dikembangkan disesuaikan dengan visi dan misi institusi, serta tujuan penyelenggaraan pendidikannya dan standar kompetensi lulusan yang telah ditetapkan; 3) Program Ma’had Al-Jami’ah dikelola unit pelaksana teknis di bawah koordinasi wakil Rektor bidang kemahasiswaan; 4) strategi yang dapat dilakukan untuk mewujudkan model manajemen Ma’had Al-Jami’ah yang relevan dengan IAIN Surakarta adalah melibatkan unsur pimpinan perguruan tinggi dan Lembaga Penjaminan Mutu yang didukung dengan adanya MOU atau bekerja sama dengan pesantren-pesantren sekitar.